2006
DOI: 10.1007/11944874_7
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of Pure-Strategy Nash Equilibria in Congestion and Local-Effect Games

Abstract: Rosenthal's congestion games constitute one of the few known classes of noncooperative games possessing pure-strategy Nash equilibria. In the network version, each player wants to route one unit of flow on a single path from her origin to her destination at minimum cost, and the cost of using an arc depends only on the total number of players using that arc. A natural extension is to allow for players controlling different amounts of flow, which results in so-called weighted congestion games. While examples ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…For a general case, Rosenthal (1973b) gave an example of an asymmetric weighted network congestion game that does not have an equilibrium in pure strategies. More recently, Dunkel and Schulz (2008) strengthened this result by showing that the problem of deciding whether a weighted network congestion game with integer-splittable flows admits a PSNE is strongly NP-hard.…”
Section: Related Workmentioning
confidence: 94%
“…For a general case, Rosenthal (1973b) gave an example of an asymmetric weighted network congestion game that does not have an equilibrium in pure strategies. More recently, Dunkel and Schulz (2008) strengthened this result by showing that the problem of deciding whether a weighted network congestion game with integer-splittable flows admits a PSNE is strongly NP-hard.…”
Section: Related Workmentioning
confidence: 94%
“…On the positive side, Fotakis et al [16] and Panagopoulou and Spirakis [30] proved the existence of a PNE in games with affine and exponential costs, respectively. Dunkel and Schulz [13] showed that it is strongly NP-hard to decide whether or not a weighted congestion game with nonlinear cost functions possesses a PNE. If the strategy of every player contains a single facility only (singleton games), Fotakis et al [15] showed the existence of PNE for linear cost functions (without a constant).…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to our model, the models above allowed that a player uses a resource with multiple units of demand at the same time. It turns out that allowing for this kind of self-congestion has a severe impact on the existence of pure Nash equilibria [10,24] but for networks of parallel links it is known that pure Nash equilibria are guranteed to exist [16,28].…”
Section: Related Workmentioning
confidence: 99%